2011
DOI: 10.1128/cvi.05356-11
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Entamoeba histolytica Excretory-Secretory Antigen and Identification of a New Potential Diagnostic Marker

Abstract: Serodiagnosis of amoebiasis remains the preferred method for diagnosis of amoebic liver abscess (ALA).However, the commercially available kits are problematic in areas of endemicity due to the persistently high background antibody titers. Human serum samples (n ‫؍‬ 38) from patients with ALA who live in areas of endemicity were collected from Hospital Universiti Sains Malaysia during the period of 2008 to 2010. Western blots using excretory-secretory antigen (ESA) collected from axenically grown Entamoeba hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…In addition, some of the proteins identified in this study will help to develop diagnostic tools capable of detecting both cyst and trophozoite forms of the parasite (Tables S4, S5, S6). A recent study shows that sera of amebic liver abscess patients can recognize a 110 kDa protein (annotated as pyruvate phosphate dikinase, EHI_009530) [53]. This protein was identified in all 5 cyst samples in our study (see Table 2 or Table S3), supporting the notion that proteins identified in this study have promise as candidate diagnostic targets.…”
Section: Discussionsupporting
confidence: 87%
“…In addition, some of the proteins identified in this study will help to develop diagnostic tools capable of detecting both cyst and trophozoite forms of the parasite (Tables S4, S5, S6). A recent study shows that sera of amebic liver abscess patients can recognize a 110 kDa protein (annotated as pyruvate phosphate dikinase, EHI_009530) [53]. This protein was identified in all 5 cyst samples in our study (see Table 2 or Table S3), supporting the notion that proteins identified in this study have promise as candidate diagnostic targets.…”
Section: Discussionsupporting
confidence: 87%
“…They contribute to the virulence of the parasite by their adherence to the host tissue, and cause contact-dependent cytolysis of target cells; they are also involved in phagocytosis and contribute to resistance to cell lysis inflicted by the host [36]. The GalNAc lectin protein was also reported by Wong et al [15] as one of the components of excretory-secretory antigens of E. histolytica . In addition, the abundance of the Gal/GalNAc lectin protein on the surface of the parasite and its antigenic property have allowed it to be used for antigen detection in the TechLab Entamoeba histolytica II ELISA kit (TechLAB Inc.) [37].…”
Section: Resultsmentioning
confidence: 99%
“…The E. histolytica Gal/Gal-NAc lectin antigen is being utilized in commercial antigen detection tests such as the TechLab E. histolytica II ELISA (TechLab Inc). A study on ES proteins showed the diagnostic potential of pyruvate phosphate dikinase (PPDK), and its recombinant form has been used to develop a lateral flow dipstick test [15, 16]. In terms of treatment, auronofin has been identified as an effective drug which targets thioredoxin reductase, an ES protein of E. histolytica [17].…”
Section: Introductionmentioning
confidence: 99%
“…Thus similar observation may be expected ESA. Western blot analysis using patients serum samples revealed the high diagnostic value of native and recombinant forms of PPDK for detection of ALA [16,17]. Since PPDK is a component of E. histolytica ESA, it is conceivable that it may be also useful as a target for detection of this parasite in stool sample.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile E. histolytica excretory-secretory antigens (EhESA) was produced using the method we have described earlier [17]. New Zealand white rabbits (Oryctolagus cuniculus; female, 2.8-3.0 kg, 11-13 weeks old) were used for immunizations, with electro-eluted rPPDK, or E. histolytica ESA.…”
Section: Production and Purification Of Polyclonal Antibodiesmentioning
confidence: 99%